2(5z-1)-2(6-2z)=4

Simple and best practice solution for 2(5z-1)-2(6-2z)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5z-1)-2(6-2z)=4 equation:


Simplifying
2(5z + -1) + -2(6 + -2z) = 4

Reorder the terms:
2(-1 + 5z) + -2(6 + -2z) = 4
(-1 * 2 + 5z * 2) + -2(6 + -2z) = 4
(-2 + 10z) + -2(6 + -2z) = 4
-2 + 10z + (6 * -2 + -2z * -2) = 4
-2 + 10z + (-12 + 4z) = 4

Reorder the terms:
-2 + -12 + 10z + 4z = 4

Combine like terms: -2 + -12 = -14
-14 + 10z + 4z = 4

Combine like terms: 10z + 4z = 14z
-14 + 14z = 4

Solving
-14 + 14z = 4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 14z = 4 + 14

Combine like terms: -14 + 14 = 0
0 + 14z = 4 + 14
14z = 4 + 14

Combine like terms: 4 + 14 = 18
14z = 18

Divide each side by '14'.
z = 1.285714286

Simplifying
z = 1.285714286

See similar equations:

| 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 | | -2b=10-8.58 | | 5h+9=4h+1 | | 3L+22=9l-20 | | 6-3f=18 | | 1.4t-12=-0.6t | | 1.4t-12=4x+23 | | x^2-2bx+a^2=0 | | 500+45(5)=y | | 500+45x=y | | 0.4xsquared-40x+360=0 | | z^2+4iz+5=0 | | x+5y/x | | 3(x-7)-4(x+2)=20 | | (x+5y)/x | | 4x-1=64 | | 7/11=x/45 | | 5x+0.9= | | 7x+0.2= | | 1/3(7x-1)=1/4 | | 81=9a | | 182/7+(5*11)=9a | | 12+144+20+6/7+(5*11)=9a | | 401.28+.2x=x | | -2+128=10 | | 5x-7=2x+12 | | 5x-14=x+14 | | x+13=39 |

Equations solver categories